Summary of the Third International Workshop on Clinical Tolerance. Issue 2 (1st October 2018) - Kawai, Tatsuo; Leventhal, Joseph; Wood, Kathryn; Strober, Samuel
Abstract : The Third International Workshop on Clinical Tolerance was held in Stanford, California, September 8–9, 2017. This is a summary of Workshop presentations of clinical trials designed to withdraw or minimize immunosuppressive (IS) drugs in kidney and liver transplant patients without subsequent evidence of rejection. All clinical protocols had in common the use of donor or recipient cell therapy combined with organ transplantation. Tolerance to HLA matched and mismatched living donor kidney transplants with complete withdrawal of IS drugs without subsequent rejection for up to 14 years of observation was achieved in more than 50 patients enrolled in trials in four medical centers after the establishment of transient or persistent chimerism. Complete IS drug withdrawal without chimerism was reported in a prospective trial of liver transplantation combined with injection of regulatory T cells. IS drug minimization without rejection was reported in recipients of living donor kidney transplants enrolled in the One Study consortium after injection of recipient regulatory T cells, or injection of donor regulatory monocytes or dendritic cells. In conclusion, considerable progress has been made in achieving IS drug withdrawal after cell therapy in recipients of organ transplants. Abstract : The authors provide a summary of the Third International Workshop on Clinical Tolerance in which the risks and benefits of tolerance induction protocols in humans were presented and discussed by protocol investigators.